2005
DOI: 10.1029/2005gl023982
|View full text |Cite
|
Sign up to set email alerts
|

Temperature difference across the Lomonosov Ridge: Implications for the Atlantic Water circulation in the Arctic Ocean

Abstract: Drifting buoy observations in the Arctic Ocean indicate that, unlike climatological conditions, the temperature of the upper Atlantic water was higher in the Makarov Basin side of the Lomonosov Ridge than in the Amundsen Basin side in 2004. Hydrographic data from 1991 to 2004 has been compared with climatology to examine the relative phase of Atlantic water temperature change in these regions. On the Amundsen Basin side of the Lomonosov Ridge, a positive temperature anomaly in the Atlantic water began in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…Our estimation shows this spatial feature is not attributable to the AW jet migration across the Eurasian flank of the Lomonosov Ridge because the magnitude of δ here is much smaller than the magnitude of the anomaly. The low magnitude of δ near the North Pole is also confirmed by aerial hydrographic CTD surveys from 2002 to 2006 [see, e.g., Kikuchi at al. , 2005].…”
Section: Comparison Of the 2005 Along‐margin Transect With Atlantic Wsupporting
confidence: 55%
“…Our estimation shows this spatial feature is not attributable to the AW jet migration across the Eurasian flank of the Lomonosov Ridge because the magnitude of δ here is much smaller than the magnitude of the anomaly. The low magnitude of δ near the North Pole is also confirmed by aerial hydrographic CTD surveys from 2002 to 2006 [see, e.g., Kikuchi at al. , 2005].…”
Section: Comparison Of the 2005 Along‐margin Transect With Atlantic Wsupporting
confidence: 55%
“…This suggests that the warm Atlantic water entering the Makarov Basin in the 1990s (Carmack et al, 1995) now had circulated around the basin and was moving along the Lomonosov Ridge towards Siberia. A similar interpretation was made earlier by Kikuchi et al (2005). In the Amundsen Basin and over the Lomonosov Ridge, the lower tempera- Rudels et al, 1994.…”
Section: Time Variability In the Eurasian Basinsupporting
confidence: 53%
“…The temperature of the Atlantic water on the Makarov Basin side of the Lomonosov Ridge had increased by 2004 (Kikuchi et al, 2005), and the observations from Oden 2005 indicated that the temperatures at the Makarov Basin side were as high, or even higher than, on the Amundsen Basin side (see Figs. 1 and 13).…”
Section: Changes In the Fram Strait Inflow Branchmentioning
confidence: 99%
“…Lags in water properties occur in part because, even if circulation remained constant, the transit times required to move a changed water property through the basin are measured in years [Polyakov et al, 2005]. For example, a 7-year lag between Atlantic water temperature rise in the Makarov Basin and that initially seen at the North Pole was found by Kikuchi et al [2005]. More importantly, the time for the ocean circulation to adjust baroclinically to a change in wind forcing is long.…”
Section: Discussionmentioning
confidence: 99%